Study on the Dynamics Virtual Simulation of the Transmission System of a Type Helicopter - Jiang Lingli; Hua Dengrong; Li Xuejun; Wang Ping (Jixie chuandong)
The transmission system is the key components of the helicopter,the study and analysis of the dynamics characteristic and virtual simulation have an important function for the whole life cycle in every stage.The 3D model of the helicopter transmission system is established by CATIA software,the load under the typical working condition is calculated,and the virtual prototype model is built under ADAMS software. The kinematic simulation analysis of the model is carried out,the rotate velocity and the time and frequency domain curves of meshing force of the main meshing gear are extracted and analyzed,the simulation results are consistent with theoretical calculation results. The research work can provides the model and theoretical basis for structure optimize design and analysis of fatigue and forecasting life of the helicopter transmission system.